A decrease in cellular microRNA-27a content is involved in azacytidine-induced P-glycoprotein expression in SKM-1 cells. (October 2016) - Messingerova, Lucia; Imrichova, Denisa; Kavcova, Helena; Seres, Mario; Sulova, Zdena; Breier, Albert
Abstract: We established an azacytidine (AzaC)-resistant human acute myeloid leukemia (AML) cell line (SKM-1/AzaC) by culturing SKM-1 cells in the presence of increasing amounts of AzaC for six months. Because AzaC is not a substrate of P-glycoprotein (a product of the ABCB1 gene; ABCB1), ABCB1 was not responsible for AzaC resistance; nevertheless, it was notably upregulated in SKM-1/AzaC cells. In addition, the transcription of the Nfkb1 gene, which encodes a member of the canonical NF-kappaB regulatory pathway, was downregulated, and the transcription of the Nfkb2 gene, which encodes a member of the non-canonical NF-kappaB regulatory pathway, was upregulated in SKM-1/AzaC cells. Here, we investigate whether miRNA-27a and miRNA-138 (both of which are known to be regulators of ABCB1 expression) are involved in the regulation of ABCB1 expression in SKM-1/AzaC cells. We observed decreased levels of miRNA-27a but of not miRNA-138 in SKM-1/AzaC cells compared with SKM-1 cells. The transfection of SKM-1/AzaC cells with a miRNA-27a mimic induced the downregulation of the ABCB1 mRNA. This was associated with an increase in Nfkb1 and a decrease in Nfkb2 transcript levels in SKM-1/AzaC cells. Taken together, these data indicate that the downregulation of miRNA-27a is involved in the upregulation of ABCB1 expression in SKM-1/AzaC cells, and this effect is associated with a switch between the canonical and non-canonical NF-kappaB pathways. Graphical abstract: Highlight: MDR SKM-1/AzaC cell variant by long-term passaging with AzaC was established. Massive overexpression of P-gp in SKM-1/AzaC cells was observed. Downregulation of miRNA-27a in SKM-1/AzaC cells was detected. Downregulation of P-gp by transfection of these cells with miRNA-27a was observed.